2023
DOI: 10.20452/pamw.16397
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of shear wave elastography for lacrimal gland evaluation in primary Sjögren's syndrome

Abstract: The present study is the first attempt to assess if shear wave elastography (SWE) of lacrimal glands can be used to support the diagnosis of primary Sjögren's syndrome. Primary Sjögren's syndrome (pSS) not only manifests itself as a "sicca syndrome", characterized by ocular and oral dryness, but also includes a variety of extraglandular manifestations. As a result, appropriate diagnosis of pSS still poses a challenge. The current classification criteria for pSS include only functional tests (Schirmer's test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Świecka et al conducted a study that included 108 healthy controls and 45 patients with PSS 60 . When compared to the control group, the SWE values for the lacrimal glands were considerably greater in the PSS patients.…”
Section: Application Of Different Imaging Examinations In the Evaluat...mentioning
confidence: 99%
“…Świecka et al conducted a study that included 108 healthy controls and 45 patients with PSS 60 . When compared to the control group, the SWE values for the lacrimal glands were considerably greater in the PSS patients.…”
Section: Application Of Different Imaging Examinations In the Evaluat...mentioning
confidence: 99%
“…Lacrimal glands often exhibit elevated SWE values, which suggest the presence of fibrotic changes. SWE parameters are associated with several clinical features, including OSDI (Ocular Surface Disease Index), ESSPRI (EULAR Sjögren's Syndrome Patient Reported Index), and the occurrence of dry eye [24][25][26]. Studies have also demonstrated the utility of ultrasonography in differentiating neoplastic lesions within the lacrimal gland, such as lymphoma or non-epithelial lesions.…”
Section: Ultrasound Of Lacrimal Glands and Labial Salivary Glandsmentioning
confidence: 99%